Pengaruh Kinerja Keuangan dan Kinerja Non-Keuangan Terhadap Return Saham Perusahaan Perkebunan di Indonesia - Ahmad Syarif; Bisma Maulana (Journal of Trends Economics and Accounting Research, 2022)
The trade war phenomenon between the United States and China, the increase in CPO import prices by CPO importing countries, and the Covid-19 pandemic have negatively impacted global trade performance. Even so, Plantation companies continue to experience an increase in stock performance and become a force of economic growth for Indonesia, thus increasing the number of young investors to invest in these companies. This makes researchers want to know the factors that support the increase in stock performance, seen from financial performance and non-financial performance. Financial performance in this study is Return on Asset (ROA) and Total Asset Turnover (TATO), while non-financial performance is Corporate Social Responsibility (CSR). This study uses quantitative methods to process data from annual reports and sustainability reports. The samples in this study were 12 Agriculture and Plantation companies in Indonesia. The results of this study indicate that CSR has no significant effect on stock returns, ROA has a significant effect on stock returns, and TATO has no significant effect on stock returns. These results expect companies to be able to maintain their financial performance on a positive trend and strategise so that stock prices continue to increase